2021
DOI: 10.48550/arxiv.2103.13713
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nonlinear inviscid damping and shear-buoyancy instability in the two-dimensional Boussinesq equations

Abstract: We investigate the long-time properties of the two-dimensional inviscid Boussinesq equations near a stably stratified Couette flow, for an initial Gevrey perturbation of size ε. Under the classical Miles-Howard stability condition on the Richardson number, we prove that the system experiences a shear-buoyancy instability: the density variation and velocity undergo an O(t −1/2 ) inviscid damping while the vorticity and density gradient grow as O(t 1/2 ). The result holds at least until the natural, nonlinear ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…For the analogous problem in the viscous setting or even in the compressible case, we refer to [5,3,4,19,53,18,1] for a comprehensive but not exhaustive list of references. Similar analysis have been also carried out recently for the Boussinesq system, see for example [9,10,25,55,66,67].…”
Section: Introduction and Main Resultssupporting
confidence: 57%
“…For the analogous problem in the viscous setting or even in the compressible case, we refer to [5,3,4,19,53,18,1] for a comprehensive but not exhaustive list of references. Similar analysis have been also carried out recently for the Boussinesq system, see for example [9,10,25,55,66,67].…”
Section: Introduction and Main Resultssupporting
confidence: 57%
“…(2) We may view Theorem 1.1 as a global stability result (in the class of axisymmetric perturbations satisfying (1.3)) for uniformly rotating solutions U rot = r e θ in cylindrical coordinates (r, θ, z) to the incompressible 3d Euler equations (1.1). From this perspective, our result connects with the study of stability of infinite energy solutions to the 2d Euler equations, such as shear flows [5,38,39,52] or stratified configurations [4], even though the stability mechanism ("phase mixing") in these settings is different. However, to the best of our knowledge there are no such results for the Euler equations in 3d.…”
Section: Introductionmentioning
confidence: 54%
“…Thus the infinite-in-time growth estimate (3.23) directly implies that any such steady state (with zero density) is nonlinearly unstable, in the sense that for any 0 < k 0 1, an arbitrarily small perturbation ρ 0 = k 0 cos(x 1 ), ω 0 = ω s leads to lim t→∞ ω(t) L 1 = ∞. See [3,5,14,17,41,45,48] for more results on stability/instability of steady states of the inviscid or viscous Boussinesq equations.…”
Section: 2mentioning
confidence: 94%
“…In the absence of thermal diffusion, the first global-intime regularity results were obtained by Hou-Li [29] in the space (u, ρ) ∈ H m (R 2 ) × H m−1 (R 2 ) for m ≥ 3, and Chae [6] in the space H m (R 2 ) × H m (R 2 ) for m ≥ 3. When Ω ⊂ R 2 is a bounded domain, Lai-Pan-Zhao [36] proved global well-posedness of solutions in H 3 (Ω)×H 3 (Ω) with noslip boundary condition, and showed that the kinetic energy is uniformly bounded in time. The function space was improved by Hu-Kukavica-Ziane [30] to (u, ρ) ∈ H m (Ω)×H m−1 (Ω) for m ≥ 2, where Ω is either a bounded domain or R 2 , T 2 .…”
Section: Introductionmentioning
confidence: 99%